Towards Achieving Environmental Sustainability: The Role of Nuclear Energy, Renewable Energy, and ICT in the Top-Five Carbon Emitting Countries - Azam, Anam; Rafiq, Muhammad; Shafique, Muhammad; Yuan, Jiahai (Frontiers in Energy Research, 2022)
In the era of globalization, the incidence of global warming emerges from the issue of climate change, which attracts the attention of several scholars to attain sustainability with respect to ensuring sufficient energy access and diminishing environmental adversities. However, in view of these circumstances, this study examines the impact of nuclear energy, renewable energy and information and communication technologies (ICTs) in pollution emission reduction for top-five emitter countries, covering the data from the period from 1995-2017. This study employs an advanced panel quantile regression model that takes into account both unobserved individual heterogeneity and distributional heterogeneity. Our outcome supports the notion that nuclear energy consumption is insignificant in contributing to less environmental pollution. With respect to the results of renewable energy consumption and ICT, both factors correct the environmental pollution in five emitter countries. These interesting findings offer significant policy understanding and suggestions based on this conclusion for these countries to ensure energy security alongside environmental sustainability.